Exploring the field of NGO cooperation in Lebanon: Snapshot from the field - El Haddad, Pierre; Zardet, Véronique (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2024)
Non-governmental organizations (NGOs) in Lebanon face survival challenges that require them to cooperate. With many attempts falling short of their goals, this paper studied dysfunctions in NGO cooperation. An intervention-research methodology was adopted to accompany fifteen active organizations in framing cooperation dysfunctions and developing solutions. We identified major interorganizational dysfunctions grouped under strategy, decision-making, procedures, and language axes. The researchers then accompanied organizations in collective solution provision to improve their cooperation. Theoretical implications point towards a moderated relationship between intra and interorganizational improvements, and that interorganizational dysfunctions transfer into interorganizational cooperation level.